Nanocodelivery of 5-Fluorouracil and Curcumin by RGD-Decorated Nanoliposomes Achieves Synergistic Chemotherapy for Breast Cancer - Reza Mahmoudi; Somayeh Mohammadi; Rouzbeh Mahmoudi; Mohamad Hassan Fouani; Maryam Tajali Ardakani; Amin Hadi; Mohsen Nikseresht; Mehrzad Jafari Barmak; Farzad Karimpour; Hassan Bardania (IET Nanobiotechnology)
In the present study, arginine–glycine–aspartic acid peptide (RGD) surface functionalized liposomes (Lips) were formulated for the concomitant targeted delivery of two antineoplastic drugs, namely curcumin (Cur) and 5-fluorouracil (5FU) to breast cancer cells. The Lips’ measured size values where 50–100 nm by transmission electron microscopy (TEM) and 169 ± 10.2 nm by dynamic light scattering (DLS), which fall within the desired range required for drug delivery purposes. In this study, we assessed the antineoplastic effects of various liposomal formulations for the codelivery of Cur and 5FU to MCF-7 breast cancer cells. We evaluated two liposomal formulations (Lip–Cur–5FU) and (Lip–Cur–5FU–RGD). The treatment of MCF-7 cells with 32 µg/mL of Cur exhibited a significant (p<0.0001) drop in cell viability among the three formulations, namely Cur and 5Fu in the free form (Lip–Cur–5FU) and liposomal form (Lip–Cur–5FU–RGD); the least viability rate (9.91% ± 1.65%) corresponded to the RGD functionalized concomitantly Cur and 5Fu loaded Lips (Lip–Cur–5FU–RGD) formulation. On the other hand, liposomal Cur increased the rate of early apoptotic cell by 4.88% without altering the rate of late apoptotic cells. Furthermore, the concomitant treatment of MCF-7 cells with Cur and 5FU enhanced the overall apoptosis rate, where Cur–5FU in the RGD functionalized-liposomal form induced the highest (16.8%) apoptosis rate, while other Cur–5FU formulations, free and nonfunctionalized liposomal form, induced lower apoptosis rates (10.4% and 10.9%, respectively). Collectively our results demonstrated that the implementation of RGD-functionalized Lips for the concomitant delivery of Cur and 5FU enhanced their therapeutic efficacy against this breast cancer model.